Malaysia fascinating destination (Kuala Lumpur : Lensa Film, 1995)
From the cosmopolitan charm and shopping treats of Kuala Lumpur, we'll venture to Malacca, rich in culture and history. Experience the spectacular jungle scenery and wildlife of Taman Negara. For lovers of sun and sea, our next stops take us to the island getaways of Penang, Pangkor and Langkawi, blessed wwith pristine beaches. And enjoy the timeless tradition of the ethnic peoplesof Sarawak and Sabah
Copy available in DVD format
Keywords: Malaysia -- Description and travel